2005
DOI: 10.2135/cropsci2004.0627
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cultivars onto Rice Growing Environments Using AMMI and SREG GGE Biplot Analyses

Abstract: ses were not always effective in analyzing the MET data structure. The ANOVA is an additive model that The identification of the highest yielding cultivar for a specific describes main effects effectively and determines if GE environment on the basis of both genotype (G) and genotype ϫ environment (GE) interaction would be useful to breeders and producers since interaction is a significant source of variation, but it yield estimates based only on G and environment (E) effects are does not provide insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
1
26

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(170 citation statements)
references
References 22 publications
8
135
1
26
Order By: Relevance
“…Genotype × environment interaction (GE) have shown there supremeness for delineating stability of genotypes and have partitioned variation that better aid for selection of consistent stable genotypes in many different studies (Dehghani et al, 2006;Yan et al, 2007;Sabaghnia & Sabaghpour, 2008). There are several methods for stability analysis among which GGE biplot analysis was used in the present study to deduce stability of the crop with aim to investigate the stability of seed yield in amaranths and graphically summarize and considerate the assets of G and GE interaction (Yan & Kang, 2003;Samonte et al, 2005;Dehghani et al, 2009, Balestre et al, 2009Oliveira et al, 2010;Tonk et al, 2011). Present study was undertaken for the first time to gather information about GE interaction of different amaranth genotypes for high seed yield using three year data using GGE biplot analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Genotype × environment interaction (GE) have shown there supremeness for delineating stability of genotypes and have partitioned variation that better aid for selection of consistent stable genotypes in many different studies (Dehghani et al, 2006;Yan et al, 2007;Sabaghnia & Sabaghpour, 2008). There are several methods for stability analysis among which GGE biplot analysis was used in the present study to deduce stability of the crop with aim to investigate the stability of seed yield in amaranths and graphically summarize and considerate the assets of G and GE interaction (Yan & Kang, 2003;Samonte et al, 2005;Dehghani et al, 2009, Balestre et al, 2009Oliveira et al, 2010;Tonk et al, 2011). Present study was undertaken for the first time to gather information about GE interaction of different amaranth genotypes for high seed yield using three year data using GGE biplot analysis.…”
Section: Introductionmentioning
confidence: 99%
“…1). In comparison, a GGE biplot analysis of six genotypes in 12 environments in Texas explained 77% of the variation in grain yield due to GGE (Samonte et al 2005). The difference in the variation due to GGE can be attributed to the diverse environments across five states and the large number of genotypes evaluated.…”
Section: Anova and Gge Biplot Analyses Of Main Crop Grain Yieldmentioning
confidence: 93%
“…This revealed the instability of yield performance and demonstrated the difficulty in identifying the highest yielding genotype for a specific location or group of locations. Samonte et al (2005) reported significant GE interaction when six cultivars were grown in 12 environments (3 yr)4 locations) and used additive main effects and multiplicative interactions (AMMI) and GGE biplot analyses to identify the highest yielding cultivar for specific environments in Texas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al (2000) classified the winter wheat environment of Ontario Canada into two; western and southern Ontario, a major winter mega-environment and eastern Ontario, a minor mega-environment. Samonte et al (2005) identified mega-environments, superior rice cultivars and ideal rice cultivars in different mega-environments using site regression GGE biplot. More recently, Yan and Holland (2010) demonstrated the appropriateness of the use of heritability-adjusted (Scale = 2) GGE (HA-GGE) biplot in simultaneous evaluation of genotypes and test locations.…”
Section: Multi-environment Analysismentioning
confidence: 99%